Green photoluminescence in TbxSc1-xBO3 solid solution - Kokh, Alexander E.; Kuznetsov, Artem B.; Svetlichnyi, Valerii A.; Rakhmanova, M. I.; Klimov, A. O.; Kokh, Konstantin A. (Journal of luminescence)
A wide range of solid solutions based on TbBO3 (with ScBO3 ≤ 30 mol%) and ScBO3 (with TbBO3 ≤ 50 mol%) was found in the TbBO3-ScBO3 system. Under UV excitation the characteristic green emission is visible due to the typical 5D4-7F5 transition of Tb3+. The intensity of photoluminescence significantly depends on the doping concentration of Tb3+ and the optimal concentration has been determined as x = 0.05. Crucial impact of hydrogen treatment on the luminescent properties was found. The compositions of TbxSc1-xBO3 (x = 0.05-0.1), after being treated with hydrogen at a temperature of 800 ◦C, has high potential for practical application as a green phosphor. This is due to its impressive quantum yield value of up to 69 % when excited by a 378 nm.